Advanced Topics on Crystal Growth - Olavo Ferreira, Sukarno (IntechOpen, 2013)
Crystal growth is the key step of a great number of very important applications. The development of new devices and products, from the traditional microelectronic industry to pharmaceutical industry and many others, depends on crystallization processes. The objective of this book is not to cover all areas of crystal growth but just present, as specified in the title, important selected topics, as applied to organic and inorganic systems. All authors have been selected for being key researchers in their field of specialization, working in important universities and research labs around the world. The first section is mainly devoted to biological systems and covers topics like proteins, bone and ice crystallization. The second section brings some applications to inorganic systems and describes more general growth techniques like chemical vapor crystallization and electrodeposition. This book is mostly recommended for students working in the field of crystal growth and for scientists and engineers in the fields of crystalline materials, crystal engineering and the industrial applications of crystallization processes.